MEANING STRUCTURE AND SPEECH FUNCTIONS OF MANGANDUNG PABAGAS BORU IN ANGKOLA WEDDING TRADITION - Hennilawati; Srimaharani Tanjung; Ernawati Br Surbakti (Indonesian EFL Journal, 2026)
This study examines the meaning structure and speech functions of mangandung pabagas boru, an oral lament performed by Angkola brides during wedding ceremonies. While previous research on Batak andung traditions has largely emphasized musical form, ritual sequence, and general cultural description, the semantic organization and communicative functions of mangandung in the context of kinship and gender socialization remain underexplored. Drawing on speech act theory and Peircean semiotics within an ethnographic approach, this research analyzes recorded performances of mangandung pabagas boru alongside in‑depth interviews with expert performers and community elders. Data were collected through participant observation, audio recording, and ethnographic interviewing in several Angkola communities. The analysis demonstrates that mangandung simultaneously realizes expressive and directive speech acts: it articulates the bride’s grief, affection, and anxiety at separation from her natal family, while also conveying moral instruction and social expectations for her future role as wife, daughter‑in‑law, and mother. Key lexical items and metaphors—such as holong (deep familial affection), tarpaina (motherly capability), and honas (being under the gaze of many eyes)—encode local wisdom regarding kinship obligations, female virtue, and community surveillance. As an indexical ritual performance, mangandung publicly marks the bride’s transition to married status and affirms continuing ties to her natal kin. The study argues that revitalising this tradition is crucial not only for cultural preservation but also for maintaining indigenous systems of moral education embedded in ritual discourse.